DESAIN SISTEM PEMERINTAHAN PRESIDENSIAL YANG EFEKTIF - Retno Saraswati (Faculty of Law, Universitas Diponegoro, 2012)
Constitutionally Indonesia adopted a presidential system of government, proportional electoral system and embrace multi-party system. Until now, the democratic government built yet stable, this is not apart from the three buildings is not compatible. The formulation of the constitution mandated a presidential system proved difficult in practice, even walking is less effective especially supported by the weak performance and presidential institution in maintaining political stability. Thus the need to design an effective presidential system of government with an realignment both institutional and non institutional.Keywords : Design, presidential system, effective.